Pemanfaatan Aplikasi Digital Dalam Peningkatan Kompetensi Guru Membuat Media Pembelajaran - Hasrian Rudi Setiawan (Yayasan Rahmat Islamiyah, 2023)
The aim of this activity is to increase teacher competence in creating learning media by utilizing digital applications. The methods used in community service activities are generally divided into two, namely: 1) Methods used to collect data related to partner needs and program success achievements; 2) The method used to carry out this community service program (PKM). The achievements of the community partnership program (PKM), in general, are providing results in increasing the competence of teachers in creating learning media with the help of digital applications. Of the participants who took part in this activity, 81% of teachers had the skills to create learning media using digital applications.